Organocatalytic Enantioselective Michael Addition of 3‐Indolinone‐2‐Carboxylates to Maleimides. Issue 11 (22nd March 2018) - Yarlagadda, Suresh; Reddy, C. Ravikumar; Ramesh, Boora; Kumar, G. Ravi; Sridhar, B.; Reddy, B. V. Subba
Abstract : An organocatalyzed asymmetric conjugate addition of 2‐substituted 3‐indolinones to maleimides has been developed by using a chiral bifunctional squaramide derived from quinidine to promote the reaction. This method provides easy access to 3‐indolinone‐2‐carboxylate‐succinimide adducts in high yields with excellent diastero and entantioselectivities and is a useful approach for the construction of vicinal quaternary‐tertiary chiral centers. In addition, product4l was successfully converted into a chiral indoline‐pyrrolidine adduct. Abstract : The asymmetric conjugate addition of 2‐substituted 3‐indolinones to maleimides has been achieved by using a chiral bifunctional squaramide as an organocatalyst. This method provides easy access to 3‐indolinone‐2‐carboxylate‐succinimide adducts in high yields with exellent diastereo‐ and enantioselectivities.